Unusual Localization of Pennella Sp. in Swordfish (Xiphias gladius) Hearts - Davide Mugetti; Elena Colombino; Vasco Menconi; Fulvio Garibaldi; Walter Mignone; Andrea Gustinelli; Marino Prearo; Franco Guarda; Maria Teresa Capucchio (Animals, 2021)
The genus Pennella comprises hematophagous parasites of marine aquatic species, including cephalopods, marine mammals, and pelagic fish. Nine species have been officially included in the genus Pennella plus another six species inquirendae. They are most often found in the host’s musculature, without penetrating internal organs. For the present study, 83 hearts from swordfish (Xiphias gladius) caught in the Mediterranean Sea were sampled and immediately fixed in formalin for histopathological analysis. In total, 10 (12.05%) hearts were found to be parasitized by copepods of the genus Pennella. Macroscopically, there was mild-to-severe fibrinous pericarditis with atrial wall thickening and multiple parasitic nodules. Histologically, the parasitic nodules were surrounded by an inflammatory-necrotizing reaction. Parasitic infestation by Pennella spp. is common in pelagic fish and in swordfish, in particular. Here, however, we report atypical cardiac localization. A future area of focus is the evaluation of cardiac Pennella spp. infestation by histopathology and genetic identification of the parasites.